1997
DOI: 10.1093/brain/120.12.2259
|View full text |Cite
|
Sign up to set email alerts
|

Origin and propagation of interictal discharges in the acute electrocorticogram. Implications for pathophysiology and surgical treatment of temporal lobe epilepsy

Abstract: Although acute electrocorticography (ECoG) is routinely performed during epilepsy surgery there is little evidence that the extent of the discharging regions is a useful guide to tailoring the resection or that the findings are predictive of outcome or pathology. Patterns of discharge propagation have, however, rarely been considered in assessing the ECoG. We hypothesize that regions where discharges show earliest peaks ('leading regions') are located in the epileptogenic zone, whereas sites in which late, sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
158
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(173 citation statements)
references
References 62 publications
(72 reference statements)
9
158
1
3
Order By: Relevance
“…26,39 Moreover, some studies have indicated that SelAH has better neuropsychological outcomes 6,14 and a lower risk of visual field defects 22 than ATL. On the other hand, some investigators have recorded neocortical epileptiform spikes with cortical electrodes, 1,35 indicating that tailored resection of the temporal neocortex is Selective amygdalohippocampectomy versus anterior temporal lobectomy in the management of mesial temporal lobe epilepsy: a meta-analysis of comparative studies essential for MTLE. Other studies have suggested that better seizure outcomes were achieved in patients who underwent ATL than in those who underwent SelAH, 3,21 and that no significant differences in neuropsychological outcomes were found between the surgical strategies.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…26,39 Moreover, some studies have indicated that SelAH has better neuropsychological outcomes 6,14 and a lower risk of visual field defects 22 than ATL. On the other hand, some investigators have recorded neocortical epileptiform spikes with cortical electrodes, 1,35 indicating that tailored resection of the temporal neocortex is Selective amygdalohippocampectomy versus anterior temporal lobectomy in the management of mesial temporal lobe epilepsy: a meta-analysis of comparative studies essential for MTLE. Other studies have suggested that better seizure outcomes were achieved in patients who underwent ATL than in those who underwent SelAH, 3,21 and that no significant differences in neuropsychological outcomes were found between the surgical strategies.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…However, the non-AT dipoles were obviously reduced in the two patients with excellent seizure outcome; thus we believe that the non-AT localization was caused by remote activity propagated from the medial temporal epileptogenic area, and removal of the medial structures resulted in spike disappearance. Interictal cortical spikes can be propagated from the primary leading region near the epileptogenic area to remote secondary regions (4). Interictal spike propagations from deep to superficial temporal, anterior to posterior temporal, and temporal to frontal lobes were observed in spike-averaging studies (2,3).…”
Section: Fig 2 Continuedmentioning
confidence: 99%
“…Scalp-recorded EEG has been used to investigate interictal spike propagation (2,3). Intracranial EEG has revealed that leading spikes near the epileptogenic area may propagate over various neocortical areas (4,5). Therefore, the interictal spike area is usually more extensive than the epileptogenic area (1).…”
mentioning
confidence: 99%
“…[1][2][3] The overall prevalence of nonlesional epilepsy in all surgical studies is B26%. 4 At present, surgical management of MRInegative pharmacoresistant focal epilepsy patients relies heavily on invasive intracranial electroencephalography, which is based on complimentary review of other noninvasive modalities including positron emission tomography, ictal single-photon emission computed tomography, and magnetoencephalography when available.…”
mentioning
confidence: 99%